Akselerasi Program Inovasi Pendidikan dan Peran Monitoring Evaluasi di Era Globalisasi - Ariesi Apriyanti; Fajri Ismail; Mardiah Astuti (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
This study aims to examine the acceleration strategy of the education innovation programs and the role of monitoring and evaluation in improving the effectiveness of education in the era of globalization. A field study was conducted at five secondary schools in SD Negeri 35 Palembang that are implementing a technology-based innovation program and a contextual curriculum. The method used was a descriptive qualitative approach with interview, observation, and documentation techniques. The results showed that effective acceleration strategies include regular teacher training, technology utilization, and cross-sector cooperation. Monitoring and evaluation carried out systematically has a positive impact on improving the quality of innovation program implementation. The success of innovation is largely determined by school leadership, organizational culture, government policy support, and community involvement. This research enhances our practical and theoretical comprehension of accelerating and evaluating educational innovations. This research focuses on effectively accelerating and evaluating educational innovations in the era of globalization.